Answer:
The solution is x=3 , y=-4 or (3,-4)
Step-by-step explanation:
Given equations (1 and 2) are:
![3x- 2y = 17\\-2x -5y = 14](https://tex.z-dn.net/?f=3x-%202y%20%3D%2017%5C%5C-2x%20-5y%20%3D%2014)
To solve a system of equation with elimination method, the co-efficients of one of the variables has to be equated and then the equations are added or subtracted to get an equation in one variable.
Multiplying equation 1 by 2:
![2(3x-2y) = 2*17\\6x-4y = 34\ \ \ \ \ Eqn\ 3](https://tex.z-dn.net/?f=2%283x-2y%29%20%3D%202%2A17%5C%5C6x-4y%20%3D%2034%5C%20%5C%20%5C%20%5C%20%5C%20Eqn%5C%203)
Multiplying equation 2 by 3
![3(-2x-5y) = 3*14\\-6x-15y = 42\ \ \ \ Eqn\ 4](https://tex.z-dn.net/?f=3%28-2x-5y%29%20%3D%203%2A14%5C%5C-6x-15y%20%3D%2042%5C%20%5C%20%5C%20%5C%20Eqn%5C%204)
Adding equation 3 and 4
![(6x-4y) + (-6x-15y) = 34+42\\6x-4y-6x-15y = 76\\-19y = 76\\\frac{-19y}{-19} = \frac{76}{-19}\\y = -4\\](https://tex.z-dn.net/?f=%286x-4y%29%20%2B%20%28-6x-15y%29%20%3D%2034%2B42%5C%5C6x-4y-6x-15y%20%3D%2076%5C%5C-19y%20%3D%2076%5C%5C%5Cfrac%7B-19y%7D%7B-19%7D%20%3D%20%5Cfrac%7B76%7D%7B-19%7D%5C%5Cy%20%3D%20-4%5C%5C)
Putting y = -4 in equation 1
![3x-2(-4) = 17\\3x+8 = 17\\3x = 17-8\\3x = 9\\\frac{3x}{3} = \frac{9}{3}\\x = 3](https://tex.z-dn.net/?f=3x-2%28-4%29%20%3D%2017%5C%5C3x%2B8%20%3D%2017%5C%5C3x%20%3D%2017-8%5C%5C3x%20%3D%209%5C%5C%5Cfrac%7B3x%7D%7B3%7D%20%3D%20%5Cfrac%7B9%7D%7B3%7D%5C%5Cx%20%3D%203)
Hence,
The solution is x=3 , y=-4 or (3,-4)
50*.6=30
so if you solve this equation it would be 30 dogs in the shelter
<h3> - - - - - - - - - - - - - ~<u>Hello There</u>!~ - - - - - - - - - - - - -
</h3>
➷ When it comes to dividing fractions, there is a rule you must now.
It's called Keep Flip Change.
I'll give you an example:
![\frac{2}{7} / \frac{4}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B7%7D%20%2F%20%5Cfrac%7B4%7D%7B6%7D)
Keep the first fraction exactly as it is
Flip the second fraction upside down (switch the numerator and denominator around)
Change the sign to a multiplication.
This is how it should look:
![\frac{2}{7} *\frac{6}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B7%7D%20%2A%5Cfrac%7B6%7D%7B4%7D)
Now you just multiply them as you normally would to get an answer of:
![\frac{12}{28}](https://tex.z-dn.net/?f=%5Cfrac%7B12%7D%7B28%7D)
➶Hope This Helps You!
➶Good Luck :)
➶Have A Great Day ^-^
↬ Hannah ♡
Answer:
1.) SSS
Step-by-step explanation:
Plug in -3 in the x.
4(2)(-3)= -24.